Metabolic behavior and prognostic value of early and end of treatment 18F-FDG PET/CT in adult Burkitt's lymphoma: the role of Deauville and IHP criteria. Issue 2 (28th January 2019) - Albano, Domenico; Bosio, Giovanni; Re, Alessandro; Pagani, Chiara; Giubbini, Raffaele; Bertagna, Francesco
Abstract: Burkitt's lymphoma is a lymphoma with unclear metabolic behavior at 18F-FDG-PET/CT and no validated criteria in treatment evaluation and prediction of outcome exist. Sixty-five patients were retrospectively included: all underwent baseline 18F-FDG-PET/CT, 56 interim PET/CT (iPET/CT) and 54 end of treatment PET/CT (eotPET/CT) after chemotherapy. Interim and eotPET/CT results were visually interpreted according to the criteria of the IHP and Deauville-five-point-scale. Results were correlated with PFS and OS to assess and to compare the predictive value of iPET and eotPET according to each criterion. All baseline PET/CT showed increased 18F-FDG uptake in nodal and extranodal lesions. The median PFS and OS were 44.6 and 48.2 months with 3-year and 5-year PFS of 76% and 62% and 3-year and 5-year OS of 71% and 57%, respectively. EotPET/CT results using DC and IHP significantly correlate with OS and PFS; while iPET/CT did not correlated with OS and PFS.